A Comprehensive Evaluation of Nutritional Quality and Antioxidant Capacity of Different Chinese Eggplant Varieties Based on Multivariate Statistical Analysis - Jian Lyu; Ning Jin; Xianglan Ma; Xueyun Yin; Li Jin; Shuya Wang; Xuemei Xiao; Jihua Yu (Antioxidants)
Free amino acids, polyphenols, and anthocyanins were quantified in 30 Chinese eggplant varieties. Moreover, antioxidant capacity characterizations including 2, 2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), ferric-reducing antioxidant power (FRAP), and 2,2-diphenyl-1-picrylhydrazyl (DPPH) were performed. The total amino acid content of the 30 eggplant varieties ranged from 15,267.19 to 26,827.4 mg kg−1 DW. The most abundant amino acids were glutamic acid, arginine, and aspartic acid. The coefficients of variation (CV) for the 20 amino acids ranged from 5.85 to 106.14%, of which 18 free amino acids had CVs > 20%. Total polyphenol and anthocyanin contents ranged from 17,097.41 to 39,474.98 µg g−1 DW and 5.28 to 978.32 µg g−1 DW, respectively. The variability of both polyphenol and anthocyanin components was >20%, with a range of 21.25–102.89%. Chlorogenic acid was the most abundant polyphenol. The total anthocyanin content of purple eggplant varieties was significantly higher than green varieties. Of the purple eggplant varieties, V28 (‘E150725’), V30 (‘1952’), and V16 (‘Weichangqie101’) had significantly higher total anthocyanins than the other eggplant varieties. DPPH, ABTS, and FRAP assays showed peaks at V3 (‘Zhengqie924’). Pearson’s correlation analysis revealed that polyphenols and anthocyanins were the main contributors to the antioxidant capacity of eggplants. A classification model with principal component analysis classified 30 Chinese eggplant varieties into two categories: high and low antioxidant capacities. The top five Chinese eggplant varieties ranked for amino acids, antioxidants, and antioxidant capacity were V29 (‘Zhengqie903’), V24 (‘Zhengqie78’), V1 (‘1871’), V3 (‘Zhengqie924’), and V28 (‘E150725’). These findings provide theoretical basis for high-quality breeding and producer/consumer selection of eggplants.